Fuzzy logic control of five-DOF active magnetic bearing system based on sliding mode concept - Saha, Sudipta; Amrr, Syed Muhammad; Bhutto, Javed Khan; AlJohani, Anas Ayesh; Nabi, M. (Frontiers in Control Engineering, 2022)
In rotor dynamics, the deviation of the shaft is a common phenomenon. The main reasons for the deviation are nonlinear attractive forces, harmonic disturbances, system parameter variations, etc. Active magnetic bearings (AMB) are employed to support the rotor inside airgap in rotating machines, thus avoiding wear and tear and also possible breakdowns. This paper proposes a fuzzy sliding mode inspired control (FSMIC) technique for the five degrees of freedom (DOF) AMB system in the presence of system uncertainties and measurement noises. The fuzzy logic is used to estimate the auxiliary control input of the sliding mode control (SMC) to attenuate the chattering. The variable gains are designed with the help of superintended fuzzy logic to bring more flexibility in the controller performance. The stability analysis is presented with the help of the Lyapunov function candidate. The simulation studies for the AMB system under distinct types of control techniques, i.e., PID, SMC, and FSMIC, illustrate the effectiveness of the proposed control strategy.